Sintesis Bioplastik dari Ampas Tebu dan Gelatin Ekstrak Tulang Ayam dengan Menggunakan Plasticizer Sorbitol - Muhammad Luthfi Ramadhan; Anfasa Mulky El-syarif; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2026)
Plastic waste is a serious problem in Indonesia, with a total of 359.06 tonnes of plastic waste entering the sea in 2023, making Indonesia the fifth largest contributor of plastic waste to the oceans in the world. The non-biodegradable nature of conventional plastics causes prolonged environmental pollution, necessitating environmentally friendly alternatives to plastic. This study aims to analyse the manufacturing process and productivity of bioplastics made from bagasse waste and chicken bone extract gelatin using sorbitol plasticiser as a plasticiser. This study is descriptive in nature with a quantitative data approach, with data collected through observation, experimentation, and literature review. The tests included water absorption, load resistance, pH, and organoleptic tests. The results of this study show that bioplastics have transparent brown characteristics, a slightly rough soft texture, and a distinctive sweet aroma. In addition, the bioplastic in this study also showed water absorption of 13.46%, load resistance of up to 1 kg, and a pH value of 6-7. The test results have met the standards of SNI 7188.7:2016, SNI 01-2891-1992, and ISO 13302:2003. Based on the tests conducted in this study, the bioplastic meets the criteria as an alternative to conventional plastic. This product can also contribute to reducing plastic waste while effectively utilising organic waste.